2008
DOI: 10.1016/j.nima.2008.07.055
|View full text |Cite
|
Sign up to set email alerts
|

The quest for the ideal photodetector for the next generation deep-underwater neutrino telescopes

Abstract: We review photodetectors used in present running neutrino telescopes. After a brief historical discourse the photodetector requirements for the next generation deep underwater neutrino telescopes are discussed. It is shown that large area vacuum hybrid phototubes are the closest to the ideal photodetector for such kinds of applications when compared with other vacuum phototubes.PACS: 95.55.Vj; 85.60.Ha

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…[1][2][3][4][5] The basic prerequisites of photodetectors (PDs) have been well described in a few pioneering studies based on their knowledge at that period of time which could be revealed established on the Olympic principles of Citius, Altius and Fortius corresponding to the photodetector principles of faster, more sensitive and smarter, respectively. 6 The term was proposed by G. van Aller and S.-O. Flyckt of Philips Laboratories in the year 1983.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The basic prerequisites of photodetectors (PDs) have been well described in a few pioneering studies based on their knowledge at that period of time which could be revealed established on the Olympic principles of Citius, Altius and Fortius corresponding to the photodetector principles of faster, more sensitive and smarter, respectively. 6 The term was proposed by G. van Aller and S.-O. Flyckt of Philips Laboratories in the year 1983.…”
Section: Introductionmentioning
confidence: 99%
“…The phototube had been developed especially for large scale neutrino experiments in Lake Baikal. There are copious references on the design and performance of the phototube [31][32][33]. It was really fantastic photodetector with spectacular parameters.…”
Section: Hybrid Phototube With Luminescent Screen (Hpls)mentioning
confidence: 99%
“…This became possible largely due to the successful developments of large sensitive area photodetectors-predominantly large area hemispherical classical photo-multiplier tubes (PMTs). On the other hand large-area hybrid phototubes with luminescent screens demonstrated their great performances [6,7].…”
Section: Introductionmentioning
confidence: 99%